Application of Response Surface Methodology in the Preparation of Pectin-Caseinate Nanocomplexes for Potential Use as Nutraceutical Formulation: A Statistical Experimental Design Analysis - Sajedeh Bahrani; Babak Ghanbarzadeh; Mahmoud Sowti Khiabani; Saeed Ghanbarzadeh; Hamed Hamishehkar (Tabriz University of Medical Sciences, 2018)
Background: The formation of electrostatic complexes between two types of biopolymers, sodium Caseinate (a derivative from most abundant milk protein) and Pectin (a natural hetro polysaccharide), was studied as a function of biopolymers concentrations and pH of solutions (3.9- 4.3). Method: The size and morphology of the resulted complexes were investigated by using of laser light scattering and transmission electron microscopy, respectively. Response surface methodology (A three-factor, three levels Box-Behnken design) was used for the optimization procedure with pH, pectin and sodium Caseinate concentrations as independent variables. Particle size and polydispersity index of nanocomplexes were considered as dependent variables. Results: Negatively charged nanocomplexes were produced below the isoelectric point of protein (5.4), at pH 4.1 with a suitable colloidal stability and average particle size of about 100 nm. It was found that the particle size of nanocomplexes could be controlled by changing in variables. Conclusion: In conclusion response surface methodology are simple, rapid and beneficial approach for preparation, optimization and investigation of the effect of independent variables on the properties of products.